Study on good characteristic of online boutique among STML final year student satisfaction - Marzuki, Marziah; Romli, Azizi (Universiti Utara Malaysia, 2020)
The purpose of this paper is to study on good characteristic of online boutiques among STML final year students satisfaction. Data collected from 100 respondents focused on students of UUM from School of Technology Management and Logistics (STML). This research involved the final year students in the STML to know their perspective about the characteristics of online boutiques that attract them to choose the boutiques. The focus of this study is to identify the goodness of the three major variables obtained from literature. The variables are website design, pricing and internet access that determines how consumer buy behavior reflects online shopping trends. Data collection was done by distributing the questionnaire to the respondents. Data was analyzed by using SPSS (Statistical Package for Social Science) and Excel.